Ethics for managers : philosophical foundations and business realities - Gilbert, Joseph, 1941- (Routledge, 2026)
Ethics for Managers introduces students to the philosophical underpinnings of business ethics and translates this theory into practical terms, demonstrating the moral implications of the decisions managers make. It explains the decision-making processes and constraints that managers face, regardless of their level or function. It then proceeds to show how to identify and analyze the ethical aspects of these decisions.This third edition features updated examples and references throughout. It contains new material on managing employees working from home, increased emphasis on the pattern aspects of individual decisions and on the systemic constraints that affect managers' decisions. There is a completely new chapter on artificial intelligence. This chapter explains at a basic level what artificial intelligence is, and examines its impact on decisions concerning the hiring, monitoring, evaluating, profiling and termination of employees.Student-friendly features include learning objectives at the beginning of each chapter, examples that demonstrate real-world business decisions, and end of chapter discussion questions. These discussion questions provide opportunities for applying chapter materials to actual decisions and can stimulate class discussion or serve as test questions. Students will find this compact, well-organized text a useful tool for understanding ethics in the digital age.
Previous edition: 2016.
Keywords: Business enterprises -- Moral and ethical aspects.; Business ethics.; Management -- Moral and ethical aspects.; elektronické knihy; electronic books